Quantitative Flow‐Ecology Relationships Using Distributed Lag Nonlinear Models: Large Floods in the Murray River Could Have Delayed Effects on Aquatic Macroinvertebrates Lasting More Than Three Decades. Issue 8 (21st August 2020) - Le, Chi T. U.; Paul, Warren L.; Gawne, Ben; Suter, Phillip J.
Abstract: We aimed to quantify the delayed effects of flows on aquatic ecosystems using 33 years of monitoring data on macroinvertebrates and water quality and 51 years of hydrological data, spanning 2, 300 km of the Murray River, Australia. By incorporating the delayed effects of hydrological indices, along with physicochemical variables, into generalized additive models to form distributed lag nonlinear models for macroinvertebrate richness and abundance, we found that the effects of floods on macroinvertebrates could last up to 32 years, depending on their magnitude. The models indicated that a large flood can cause an initial depression in macroinvertebrate abundance and richness, followed by a sustained increase persisting for over 25 years before returning to preflood levels. Twelve hydrological indices representing the magnitude of flow events were evaluated, with the q90/med (the 6‐monthly flow exceeded 10% of time, divided by the long‐term median) performing (slightly) better than other indices. Competing hypotheses for the mechanisms underlying the apparent long‐term effect of floods were considered, with the most plausible explanation being the flood‐mediated influx of allochthonous organic matter, especially coarse and large woody debris, that might drive the persistent change in the aquatic community. It is generally believed that macroinvertebrate communities recover quickly after floods, but our findings suggest that we may need to reconceptualize the effects that floods can have on aquatic macroinvertebrates and the communities they support, especially in the context of flow restoration and climate change. Plain Language Summary: Research is being done around the world to understand how much water is required to sustain river ecosystems, and therefore, how much can be extracted for consumptive uses such as irrigated agriculture. We used long‐term monitoring data (1980–2012) on aquatic macroinvertebrates—which includes insects, crustaceans, mussels, snails, and worms that spend all or part of their life in water—collected along 2, 300 km of the Murray River, Australia, to investigate the relationship between river flow and the health of aquatic ecosystems. These data indicate that small to medium flows might have an immediate effect through improvements in water quality, but large floods may have sizeable delayed impacts on macroinvertebrates lasting more than three decades. The number of species and overall abundance of macroinvertebrates initially decreased, due to washout, but then increased for a period of about 25 years after the historic flood of 1993, persisting throughout the Millennium drought (1996–2010). The positive legacy of floods might be due to an influx of woody debris during the event, which can provide habitat and food for macroinvertebrates until decomposition of the woody material is complete. Key Points: Long‐term data on macroinvertebrates, water quality, and hydrology in the Murray River enabled quantifying the flow‐ecology relationship Flood impacts on macroinvertebrate abundance and richness may persist for decades, while small to medium flows have indiscernible effects A flood‐induced influx of organic matter might underlie the apparent long‐term effect of floods